Exploring effects of coordination on the autonomy of regulators: energy regulators in Belgium. (June 2014) - Rommel, Jan; Verhoest, Koen
Regulatory administrations are increasingly fragmented. Regulation is produced by multi-actor multi-level constellations. Researchers have described how actors in such constellations coordinate with each other. This article explores how coordination affects the decision-making autonomy of agencies, using a case study of energy regulation in Belgium. It describes the extent of autonomy from the parent minister and explores how the regulator coordinates with other actors at multiple levels of government. The findings indicate that de facto discretion of regulators can be increased or reduced by other governmental actors besides the parent minister. This calls for the development of a 'relational perspective' on (regulatory) agency autonomy, which looks at relations with multiple actors, even when these actors have no direct principal–agent relationship with the agency. Points for practitioners: In recent decades, many Western governments have created independent regulatory agencies. The accumulation of these agencies across policy sectors and across levels of government has been associated with the creation of new coordination mechanisms. However, these trends may have certain unintended consequences. When authority is fragmented, the capacity for single actors to intervene may be reduced. Coordination may affect the de facto decision-making capacity of regulators. When agencies use inter-organizational relations to build up expertise, the autonomy vis-à-vis the parent minister may increase. However, when coordination mechanisms are based only on informal, voluntary agreements, these mechanisms may fail to compensate for all resource dependencies.